Engineering of defects in resistive random access memory devices - Banerjee, Writam; Liu, Qi; Hwang, Hyunsang (Journal of applied physics, 2020)
Defects are essential to switch the resistance states in resistive random-access memory (RRAM) devices. Controlled defects in such devices can lead to the stabilization of the switching performance, which is useful for high-density memory and neuromorphic computing applications. In contrast, uncontrolled defects in RRAM can generate randomness and increase intrinsic entropy, which are useful for security applications. In this tutorial, we explain how to engineer defects in RRAM devices. More specifically, we focus on defect engineering of the oxide layer and how the defects can affect the switching mechanism. Defect engineering processes include the doping effect, nanocrystal-based switching layer design, embedded metals in switching oxide, defective electrode design, etc. We explain how defects can improve the electrical performance of RRAM devices and the recent development of applications using defect-based RRAM devices.